An Analysis Of Legal Studies In Uncovering Crime Cases - Muhammad Fajrin Pane (Sean Institute, 2022)
Crown witnesses are seen as having the potential power in uncovering crimes. Moreover, crimes involve several actors who have developed strong bonds with each other and are closed, either through personal connections or business connections or through professional associations, such as corruption crimes. One of the efforts to tackle crime is through criminal law. Prevention of crime with criminal law is essentially also part of law enforcement efforts (especially criminal law enforcement). Even though criminal law enforcement in the context of crime prevention is not the only hope, its success is highly expected because it is in the field of law enforcement that the meaning of